Radiation's impact on PANI nanoparticles' optical and dielectric properties - Shawkat Salameh Gasaymeh; Aeshah Salem, (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
Additional information is provided regarding the precise doping processes used on PANI nanoparticle samples. This method involves polymerizing aniline monomer into conductive PANI emeraldine salt (ES) using dodecylbenzenesulfonic acid (DBSA) as an accelerator and dopant, in addition to the oxidizing agent and ionizing γ-irradiation. This fast one-step technique produces PANI straight from its monomer. The interactions in this synthesis technique stimulate the development of longer PANI chains, which improves solubility, thermal stability, and conductivity. Adding DBSA, a long-chain organic acid, as a dopant ion during γ-irradiation improves the optical and dielectric properties of the PANI nanoparticles. Thermogravimetric analysis (TGA) data confirms that the thermal stability of the PANI nanoparticles increases with larger doses of gamma radiation. In the range above 370 to 600˚C indicating some structural decomposition of the polymer backbone. This may be due to acid hydrolysis causing chain scission during the polymerization process under the impact of γ-irradiation. The direct double-doping approach using γ-rays and DBSA in a single step eliminates the requirement for the typical synthesis process for these nanomaterials with long-chain dopant ions, therefore avoiding time-consuming stages like de-doping and re-doping.